Modified non-fluorine oil and stain repellent nonwoven material and preparation method thereof

CN122980227APending Publication Date: 2026-10-27WUHAN RUITAIKE PROTECTIVE PRODUCTS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611133626.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种改性无氟防油防污非织造材料及制备方法,用于解决现有技术中非织造材料防油性能和防污性能有待进一步提高的技术问题

Benefits of technology

1、疏油接枝非织造主体与限域整理凝胶液进入同一体系后,材料表层由单一界面转变为具有连续衔接关系的复合界面,油性介质接触时,首先对应于疏油接枝非织造主体所提供的稳定表面基础,其后又受到凝胶液在纤维外缘形成的限域层持续调节,使介质在表面的润湿方式、铺展边界以及沿孔隙进一步迁移的路径均受到约束,前者负责建立初始界面状态,后者负责维持该状态在接触过程中的均一性和完整性,二者并非割裂发挥作用,而是在同一表层区域内形成前后衔接的连续配合关系,由此使材料表面在反复接触油性介质的情形下仍不易出现局部失稳或界面快速衰减。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application discloses a modified fluorine-free oil-proof and stain-proof non-woven material and a preparation method thereof, and belongs to the technical field of non-woven materials, and is used for solving the technical problem that the oil-proof performance and the stain-proof performance of the non-woven material in the prior art need to be further improved. The stable composite interface is constructed on the surface layer of the oil-proof and stain-proof non-woven material fiber through the synergistic effect of the oil-repellent grafted non-woven main body and the limited finishing gel liquid. The oil-repellent grafted non-woven main body mainly gives the material a low surface energy interface basis and inhibits the wetting and adhesion of oily dirt. The limited finishing gel liquid promotes the ordered loading, uniform distribution and stable maintenance of the functional components, and enhances the surface layer structure integrity together with tannic acid and ferric chloride, so that the oil-proof and stain-proof non-woven material has the advantages of oil-proof, stain-proof, easy dirt removal and good use stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nonwoven materials technology, specifically to a modified fluorine-free oil- and stain-resistant nonwoven material and its preparation method. Background Technology

[0002] In existing technologies, modified fluorine-free oil- and stain-resistant nonwoven materials typically use nonwoven substrates formed from natural fibers, regenerated fibers, synthetic fibers, or their mixtures as carriers. The substrate is prepared by wet web forming, air-laid web forming, or carding web forming combined with thermal bonding, chemical bonding, hydroentangling, or needle punching. Then, finishing processes such as padding, spraying, and coating are used to introduce organosilicon, long-chain hydrocarbons, or other fluorine-free low surface energy components into the fiber surface to impart certain oil- and stain-resistant properties and easy-to-clean properties to the material, thereby meeting the requirements for functional nonwoven materials in fields such as hygiene, protection, filtration, and packaging.

[0003] However, nonwoven materials are usually formed by a large number of interwoven fibers to form a loose porous network. There are many pores and connecting channels between the fibers. When oily dirt comes into contact with the material, in addition to adhering to the fiber surface, it is easy to spread, penetrate and remain along the fiber gaps and capillary channels. When existing fluorine-free finishing systems are applied to this type of material, it is often difficult to form an effective protection for the fiber surface and pore interface at the same time. As a result, the material's ability to block low surface tension oil stains is insufficient, and its oil-proof and stain-proof performance still needs to be further improved.

[0004] In addition, existing fluorine-free oil and stain repellent finishing methods are mostly achieved by the adhesion, film formation, or coating of functional components on the surface of nonwoven materials. However, the surface of nonwoven materials has large undulations and the fiber contact state is complex. During the application, drying, and heat treatment, the finishing components are prone to uneven distribution, local aggregation, or migration into the pores, which in turn affects the continuity and stability of the functional interface of the fiber surface. This makes the material prone to inconsistent protective effects and insufficient surface stain resistance during use, making it difficult to stably achieve both oil and stain repellency.

[0005] To address this technical deficiency, a solution is proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a modified fluorine-free oil- and stain-resistant nonwoven material and its preparation method, which solves the technical problem that the oil- and stain-resistant properties of nonwoven materials in the prior art need to be further improved.

[0007] The objective of this invention can be achieved through the following technical solutions: A method for preparing a modified fluorine-free oil- and stain-resistant nonwoven material includes the following steps: S1. Add tannic acid and deionized water to the finishing tank and stir until dissolved. Then add the confined finishing gel solution prepared by the cross-linking reaction of sodium carboxymethyl-β-cyclodextrin and ε-polylysine under the action of an activator and the subsequent dispersion after post-treatment and stirring. Then add 10wt% acetic acid aqueous solution to adjust the pH of the reaction system to 4.8-5.3, and then add 5wt% ferric chloride aqueous solution and stir evenly to obtain the composite finishing solution. S2. Apply an epoxy oleophobic grafting agent to an amine-activated nonwoven base web, and then perform grafting modification under alkaline conditions through impregnation, drying, and heat treatment. Place the oleophobic grafted nonwoven body into a composite finishing solution for padding, then dry at 75-85℃, and finally heat treat at 100-110℃ to obtain an oil-resistant and stain-resistant nonwoven material.

[0008] Furthermore, in step S1, the ratio of tannic acid, deionized water, confined gel solution and 5wt% ferric chloride aqueous solution is 1.6-2.4g:105-140mL:90-115mL:10-16mL. Furthermore, in step S2, the ratio of the amount of the oleophobic grafted nonwoven substrate to the composite finishing liquid is 90-110g:210-280mL.

[0009] Furthermore, the preparation method of the oleophobic grafted nonwoven body is as follows: epoxy oleophobic grafting agent, anhydrous ethanol and deionized water are added to a finishing tank and stirred. After stirring evenly, sodium bicarbonate is added, followed by amine-activated nonwoven base web impregnation. After impregnation, the liquid is rolled, and post-treatment is performed to obtain the oleophobic grafted nonwoven body.

[0010] Furthermore, the ratio of the epoxy oleophobic grafting agent, anhydrous ethanol, deionized water, sodium bicarbonate, and amine-activated nonwoven base web is 18-24g:145-185mL:18-25mL:0.6-1.0g:90-110g. The post-treatment includes drying at 90-100℃ and then heat-treating at 105-120℃ for 3-6 minutes to obtain the oleophobic grafted nonwoven body.

[0011] Furthermore, the preparation method of the amine-activated nonwoven base web includes the following steps: A1. Add cellulose short fibers, chitosan short fibers and deionized water to a dispersion tank and disperse them. After uniform dispersion, form a web to obtain a wet fiber web. A2. Add dialdehyde starch, adipic acid dihydrazide and deionized water to a mixing tank and stir. Then add 10wt% acetic acid aqueous solution to adjust the pH of the system to 4.8-5.4. Then apply it to the fiber wet web, pre-dry it at 80-90℃ after sizing, and then heat treat it at 120-140℃ to obtain amine-activated nonwoven base web.

[0012] Furthermore, in step A1, the ratio of the amount of cellulose short fiber, chitosan short fiber and deionized water is 75-88g:18-24g:3600-4600mL. Furthermore, in step A2, the ratio of the amount of dialdehyde starch, adipic acid dihydrazide, deionized water and fiber wet web is 7-10g:4-5g:180-260mL:90-110g.

[0013] Furthermore, the preparation method of the epoxy oleophobic grafting agent is as follows: polymethylhydrosiloxane and toluene are added to a reaction vessel and stirred. After stirring evenly, allyl glycidyl ether and 1-octadecene are added, followed by platinum catalyst solution. The reaction vessel is heated to 75-85℃ and stirred for 4-6 hours. After the reaction is completed, the solvent is removed under reduced pressure and filtered through a 200-300 mesh filter to obtain the epoxy oleophobic grafting agent.

[0014] Furthermore, the ratio of the polymethylhydrosiloxane, toluene, allyl glycidyl ether, 1-octadecene, and platinum catalyst solution is 45-60g:100-140mL:10-14mL:15-22mL:0.20-0.25mL.

[0015] Furthermore, the method for preparing the confined finishing gel solution is as follows: sodium carboxymethyl-β-cyclodextrin and deionized water are added to a reaction vessel and stirred until dissolved. Then, 5 wt% hydrochloric acid aqueous solution is added to adjust the pH of the system to 5.2-5.8. Subsequently, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide are added and stirred. Then, ε-polylysine is added, and the reaction is carried out at 25-35℃ with stirring for 6-10 h. After the reaction is completed, 5 wt% sodium hydroxide aqueous solution is added to adjust the pH of the system to 6.3-6.8. The confined finishing gel solution is obtained after post-treatment.

[0016] Furthermore, the ratio of sodium carboxymethyl-β-cyclodextrin, deionized water, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide, and ε-polylysine is 18-24g:270-360mL:7-10g:4-6g:5-8g. The post-treatment includes: dialyzing for 12-24h using a dialysis bag with a molecular weight cutoff of 4000-6000Da after the reaction, followed by filtration through a 200-300 mesh filter, and then shearing and dispersing at 6000-8000r / min for 8-15min to obtain a confined gel solution.

[0017] The present invention also discloses a modified fluorine-free oil- and stain-resistant nonwoven material, which is prepared by a method for preparing a modified fluorine-free oil- and stain-resistant nonwoven material.

[0018] The present invention has the following beneficial effects: 1. When the oleophobic grafted nonwoven substrate and the confined finishing gel enter the same system, the material surface changes from a single interface to a composite interface with a continuous connection. When the oily medium comes into contact, it first corresponds to the stable surface foundation provided by the oleophobic grafted nonwoven substrate, and then is continuously regulated by the confined layer formed by the gel on the outer edge of the fiber. This constrains the wetting method, spreading boundary, and further migration path of the medium on the surface. The former is responsible for establishing the initial interface state, and the latter is responsible for maintaining the uniformity and integrity of this state during the contact process. The two do not play a separate role, but form a continuous cooperation relationship in the same surface area. As a result, the material surface is not prone to local instability or rapid interface decay even when it comes into repeated contact with the oily medium.

[0019] 2. The role of the confined finishing gel in the system is not limited to covering the outer layer of the oleophobic grafted nonwoven substrate, but rather to further create a continuous and controlled surface environment based on the existing surface state of the substrate. When foreign contaminants come into contact with the material, they are first affected by the low spreading tendency of the substrate surface, and then by the continuous restriction of the gel interface on the residence position, adhesion mode and further embedding process between fibers. This keeps the contamination changes mainly at the surface stage and makes it difficult for them to evolve into the interior. At the same time, the interface does not form a loose layer that easily buries contaminants, but maintains good continuity and integrity. Therefore, after the contaminants have been present, they are not easy to form a tight and continuous binding state with the surface. The interface behavior formed in this way naturally runs through the entire process of contact, adhesion, residue and subsequent detachment.

[0020] 3. The network support provided by the oleophobic grafted nonwoven substrate and the continuous interface layer formed on the surface by the confined finishing gel liquid also establish a relatively coordinated structural matching relationship. The gel liquid tends to spread orderly along the outer edge of the fiber rather than adhering to the outer side of the substrate in an isolated stacking manner. This allows the surface functional distribution, interface bonding state and the original open characteristics of the internal network to be mutually accommodated. As the use process progresses, the substrate undertakes the overall support and surface functional support, while the gel liquid undertakes the interface regularity and state maintenance. The two form a clear division of labor and connection relationship within the same system, which is less likely to cause surface hardening, local embrittlement, interface detachment or channel imbalance. Therefore, the material is more likely to maintain structural continuity, interface stability and overall state coordination under continuous use conditions. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 This is a SEM image of the amine-active nonwoven substrate prepared in Example 3 of the present invention; Figure 2 This is a SEM image of the oleophobic grafted nonwoven body prepared in Example 6 of the present invention; Figure 3 This is a SEM image of the oil- and stain-resistant nonwoven material prepared in Example 6 of the present invention.

[0023] like Figure 1 As shown, the amine-activated nonwoven base network is formed by short fibers interlacing to form a three-dimensional porous network. The fibers are relatively uniformly dispersed, and the pore structure is continuous. No obvious agglomeration, collapse or large-area breakage was observed. The fiber intersections are tightly bonded, indicating that the overall structure of the base network is stable after finishing and heat treatment. Some fiber surfaces show certain roughening characteristics, indicating that the interface state has changed after treatment, which is conducive to demonstrating that the material has good structural integrity and a basis for subsequent functionalization. like Figure 2 As shown, the oleophobic grafted nonwoven matrix still maintains a three-dimensional porous network composed of interlaced short fibers. The overall structure is continuous, with no obvious collapse or large-area adhesion. Compared with the amine-activated nonwoven matrix, the surface roughness of the fibers has increased, and a relatively uniform adhesion layer and enhanced inter-fiber connection are visible in some areas. This indicates that the finishing agent has been stably present on the fiber surface and in the bonding area. This morphological feature shows that the grafting treatment has not damaged the pore structure of the substrate and is conducive to the formation and maintenance of the oleophobic properties of the material surface. like Figure 3 As shown, the oil- and stain-resistant nonwoven material still maintains a porous network structure composed of interwoven short fibers. The overall morphology is continuous and relatively complete, with no obvious collapse or severe adhesion. Compared with the oleophobic grafted nonwoven body, the surface roughness of the fibers is further increased, and relatively uniform coating or granular adhesion features can be seen locally. This indicates that the composite finishing components have been deposited relatively stably on the fiber surface and bonding area. The above morphological features indicate that the finishing treatment, while maintaining the porous structure of the substrate, is conducive to the formation of oil- and stain-resistant properties on the material surface. Detailed Implementation

[0024] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] In this application, the average fiber length of the cellulose short fibers used is 2.5-3.5 mm, and the linear density is 1.4-1.7 dtex; the average fiber length of the chitosan short fibers used is 2.5-3.5 mm, the linear density is 1.4-1.8 dtex, and the degree of deacetylation is 89-91%; the degree of oxidation of the dialdehyde starch used is 35-40%, and the aldehyde content is 4.5-5.2 mmol / g; the viscosity of the polymethylhydrosiloxane used at 25°C is 20-25 mPa·s, and the Si-H content is 1.53-1.62%; the platinum catalyst solution used is a 2.1 wt% platinum(0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane-o-xylene solution.

[0026] Example 1

[0027] This embodiment provides a method for preparing an oleophobic grafted nonwoven substrate, including the following steps: Step ①: Preparation of amine-activated nonwoven base web Weigh out 75.0g of cellulose short fibers, 18.0g of chitosan short fibers and 3600.0mL of deionized water and add them to a dispersion tank to disperse. After uniform dispersion, form a web to obtain a wet fiber web. Weigh out 7.0g of dialdehyde starch, 4.0g of adipic acid dihydrazide and 180.0mL of deionized water and add them to the mixing tank and stir. Then add 10wt% acetic acid aqueous solution to adjust the pH of the system to 4.8. Then apply it to 90.0g of fiber wet web, pre-dry it at 80℃ after squeezing, and then heat treat it at 120℃ to obtain amine-activated nonwoven base web.

[0028] The reaction principle for preparing amine-activated nonwoven webs is as follows: Under acidic conditions, the aldehyde groups on the dialdehyde starch molecular chain undergo a condensation reaction with the hydrazide groups in the adipic acid dihydrazide molecule to form a hydrazone linkage structure. Simultaneously, some of the aldehyde groups in the dialdehyde starch can also undergo a Schiff base reaction with the free amino groups on the chitosan molecular chain, thereby establishing chemical connections between chitosan short fibers and between chitosan and cellulose short fibers. Cellulose and chitosan themselves also maintain a network structure through hydrogen bonding between hydroxyl and amino groups and fiber entanglement. Heat treatment further promotes the above condensation reactions, resulting in a stable structure within the matrix network composed of fiber entanglement, hydrogen bonding, and covalent linkages.

[0029] Step 2: Preparation of epoxy oleophobic grafting agent

[0030] Weigh out 45.0 g of polymethylhydrosiloxane and 100.0 mL of toluene and add them to the reaction vessel. Stir until homogeneous, then add 10.0 mL of allyl glycidyl ether and 15.0 mL of 1-octadecene, followed by 0.20 mL of platinum catalyst solution. Heat the reaction vessel to 75 °C and stir for 4 h. After the reaction is complete, remove the solvent under reduced pressure and filter through a 200-mesh filter to obtain the epoxy oleophobic grafting agent.

[0031] The reaction principle for preparing epoxy oleophobic grafting agents is as follows: Under the action of a platinum catalyst, the silane-hydrogen bonds on the polymethylhydrosiloxane molecular chain undergo hydrosilylation reactions with the carbon-carbon double bonds in allyl glycidyl ether and 1-octadecene molecules, which introduce epoxy-containing organic side groups and long-chain hydrocarbon side groups into the polysiloxane backbone. This reaction mainly occurs between the silane-hydrogen bonds and the alkenyl group. The epoxy group in allyl glycidyl ether is retained in the product as a functional side group. Therefore, the resulting product is a modified polysiloxane containing both epoxy functional groups and long-chain hydrocarbon structures.

[0032] Step ③: Preparation of oleophobic grafted nonwoven substrate

[0033] Weigh out 18.0g of epoxy oleophobic grafting agent, 145.0mL of anhydrous ethanol and 18.0mL of deionized water and add them to the finishing tank. Stir until uniform, then add 0.6g of sodium bicarbonate and 90.0g of amine-activated nonwoven base web for impregnation. After impregnation, roll the liquid and dry at 90℃. Then heat treat at 105℃ for 3min to obtain the oleophobic grafted nonwoven body.

[0034] The reaction principle for preparing oleophobic grafted nonwoven substrates is as follows: In the alkaline and heated conditions, the epoxy groups in the epoxy oleophobic grafting agent undergo a ring-opening addition reaction with the amino groups contained in the chitosan segments of the amine-active nonwoven matrix, thereby forming a covalent bond between the finishing agent molecules and the matrix. This fixes the structure containing polysiloxane segments and long-chain hydrocarbon groups on the fiber surface and fiber bonding area. In addition to covalent bonding, there are also intermolecular interactions between the finishing agent molecules and the cellulose and chitosan segments, which is beneficial to the stable existence of the grafted layer on the substrate surface. The whole process is essentially a chemical grafting of an epoxy-functionalized organosilicon compound onto an amino-containing fiber substrate.

[0035] The mechanism of action of oleophobic grafted nonwovens in oil- and stain-resistant nonwoven materials is as follows: The oleophobic grafted nonwoven body obtained by this process is composed of a nonwoven base fiber skeleton and a low surface energy oleophobic structure introduced into the fiber surface and fiber bonding area. In the system, it not only serves as the main bearing layer for subsequent finishing, maintaining the original pore network, air permeability channels and mechanical support of the material, but also serves as the interface transition basis for the construction of subsequent functional layers, adjusting the surface state and interface bearing capacity of the fiber outer edge. Thus, on the one hand, it can reduce the tendency of oily media to wet, spread and migrate along the pores on the material surface, and on the other hand, it is conducive to the formation of a more uniform and stable composite covering structure of subsequent finishing components on the fiber surface, reducing interface mismatch, local defects and discontinuous functional distribution, thereby having a fundamental impact on the final comprehensive performance such as oil resistance, stain resistance, easy stain removal, air permeability and strength retention.

[0036] Example 2

[0037] This embodiment provides a method for preparing an oleophobic grafted nonwoven substrate, including the following steps: Step ①: Preparation of amine-activated nonwoven base web Weigh out 88.0g of cellulose short fibers, 24.0g of chitosan short fibers and 4600.0mL of deionized water and add them to a dispersion tank to disperse. After uniform dispersion, form a web to obtain a wet fiber web. Weigh out 10.0g of dialdehyde starch, 5.0g of adipic acid dihydrazide and 260.0mL of deionized water and add them to the mixing tank and stir. Then add 10wt% acetic acid aqueous solution to adjust the pH of the system to 5.4. Then apply it to 110.0g of fiber wet web, pre-dry it at 90℃ after squeezing, and then heat treat it at 140℃ to obtain amine-activated nonwoven base web.

[0038] Step 2: Preparation of epoxy oleophobic grafting agent

[0039] Weigh out 60.0 g of polymethylhydrosiloxane and 140.0 mL of toluene and add them to the reaction vessel. Stir until homogeneous, then add 14.0 mL of allyl glycidyl ether and 22.0 mL of 1-octadecene, followed by 0.25 mL of platinum catalyst solution. Heat the reaction vessel to 85 °C and stir for 6 h. After the reaction is complete, remove the solvent under reduced pressure and filter through a 300-mesh filter to obtain the epoxy oleophobic grafting agent.

[0040] Step ③: Preparation of oleophobic grafted nonwoven substrate

[0041] Weigh out 24.0g of epoxy oleophobic grafting agent, 185.0mL of anhydrous ethanol and 25.0mL of deionized water and add them to the finishing tank. Stir until uniform, then add 1.0g of sodium bicarbonate and 110.0g of amine-activated nonwoven base web for impregnation. After impregnation, roll the liquid and dry at 100℃. Then heat treat at 120℃ for 6min to obtain the oleophobic grafted nonwoven body.

[0042] Example 3

[0043] This embodiment provides a method for preparing an oleophobic grafted nonwoven substrate, including the following steps: Step ①: Preparation of amine-activated nonwoven base web Weigh out 81.5g of cellulose short fibers, 21.0g of chitosan short fibers and 4100.0mL of deionized water and add them to a dispersion tank to disperse. After the dispersion is uniform, the fibers are formed into a wet web. Weigh out 8.5g of dialdehyde starch, 4.5g of adipic acid dihydrazide and 220.0mL of deionized water and add them to the mixing tank and stir. Then add 10wt% acetic acid aqueous solution to adjust the pH of the system to 5.1. Then apply it to 100.0g of fiber wet web, pre-dry it at 85℃ after squeezing, and then heat treat it at 130℃ to obtain amine-activated nonwoven base web.

[0044] Step 2: Preparation of epoxy oleophobic grafting agent

[0045] Weigh out 52.5g of polymethylhydrosiloxane and 120.0mL of toluene and add them to the reaction vessel. Stir until homogeneous, then add 12.0mL of allyl glycidyl ether and 18.5mL of 1-octadecene, followed by 0.23mL of platinum catalyst solution. Heat the reaction vessel to 80℃ and stir for 5 hours. After the reaction is complete, remove the solvent under reduced pressure and filter through a 250-mesh filter to obtain the epoxy oleophobic grafting agent.

[0046] Step ③: Preparation of oleophobic grafted nonwoven substrate

[0047] Weigh out 21.0g of epoxy oleophobic grafting agent, 165.0mL of anhydrous ethanol and 21.5mL of deionized water and add them to the finishing tank. Stir until uniform, then add 0.8g of sodium bicarbonate and 100.0g of amine-activated nonwoven base web for impregnation. After impregnation, roll the liquid and dry at 95℃. Then heat treat at 113℃ for 5min to obtain the oleophobic grafted nonwoven body.

[0048] Example 4

[0049] This embodiment provides a method for preparing a modified fluorine-free oil- and stain-resistant nonwoven material, including the following steps: Step 1: Preparation of confined finishing gel solution Weigh 18.0 g of sodium carboxymethyl-β-cyclodextrin and 270.0 mL of deionized water and add them to the reaction vessel. Stir until dissolved. Then add 5 wt% hydrochloric acid aqueous solution to adjust the pH of the system to 5.2. Then add 7.0 g of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and 4.0 g of N-hydroxysuccinimide and stir. Then add 5.0 g of ε-polylysine and stir at 25 °C for 6 h. After the reaction is completed, add 5 wt% sodium hydroxide aqueous solution to adjust the pH of the system to 6.3. After the reaction is completed, dialyze the solution for 12 h using a dialysis bag with a molecular weight cutoff of 4000 Da. Then filter through a 200 mesh filter and shear disperse at 6000 r / min for 8 min to obtain a confined gel solution.

[0050] The reaction principle for preparing confined gel solutions is as follows: The carboxyl group on the sodium carboxymethyl-β-cyclodextrin molecule is first activated by 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, and forms a relatively stable active intermediate with the participation of N-hydroxysuccinimide. Subsequently, the primary amino group on the ε-polylysine molecule undergoes an amidation reaction with the activated carboxyl group, establishing an amide bond between the cyclodextrin derivative and polylysine. Since both components have multifunctional characteristics, multi-point covalent linkages and segment association structures are formed in the system. After dialysis to remove small molecule byproducts and unreacted components, it exists in a dispersed state in the aqueous phase.

[0051] The mechanism of action of confined finishing gel in oil- and stain-resistant nonwoven materials is as follows: The confined finishing gel obtained by this process is composed of multi-point action units containing cyclodextrin cavities and carboxymethyl side groups, polylysine segments, and the resulting gel-dispersed structure. In the system, it mainly acts as a confined carrier and ordered distribution medium for subsequent functional components. On the one hand, this gel structure provides local containment, segment association, and spatial constraint for the active components entering the system, reducing their disordered migration, local accumulation, and loss tendency on the fiber surface, making it easier for functional substances to form a more uniform distribution along the fiber outer edge and pore interface. On the other hand, the cyclodextrin-derived structure and polylysine segments together endow the system with certain interfacial affinity and network retention capabilities, which is beneficial for the subsequent composite surface layer to shift from discrete adhesion to continuous organization. Therefore, the influence of this gel on the final product is mainly reflected in improving the uniformity of functional layer coverage, structural integrity, and operational stability, and providing fundamental support for the synergistic maintenance of oil resistance, stain resistance, easy decontamination, and air permeability and mechanical properties.

[0052] Step 2: Preparation of oil- and stain-resistant nonwoven materials

[0053] Weigh out 1.6g of tannic acid and 105.0mL of deionized water and add them to the finishing tank. Stir until dissolved, then add 90.0mL of confined finishing gel solution and stir. Then add 10wt% acetic acid aqueous solution to adjust the pH of the reaction system to 4.8, and then add 10.0mL of 5wt% ferric chloride aqueous solution and stir evenly to obtain the composite finishing solution. Weigh out 90.0g of oleophobic grafted nonwoven body and immerse it in 210.0mL of composite finishing solution. Then dry it at 75℃ and heat treat it at 100℃ to obtain oil-proof and stain-proof nonwoven material.

[0054] The reaction principle for preparing oil- and stain-resistant nonwoven materials is as follows: The polyphenolic hydroxyl groups in tannic acid molecules coordinate with ferric ions to form a metal-polyphenol complex structure. The cyclodextrin and polylysine segments in the confined finishing gel solution form a complex relationship with this complex structure through hydrogen bonding and intermolecular association. Under the conditions of padding, drying and heat treatment, the above-mentioned coordination complex structure and complex relationship are fixed on the surface of the oleophobic grafted nonwoven substrate, so that the finishing components are attached to the substrate in the form of a composite finishing layer. This process mainly involves metal-polyphenol coordination and intermolecular complexation between the gel components and the complex structure.

[0055] Example 5

[0056] This embodiment provides a method for preparing a modified fluorine-free oil- and stain-resistant nonwoven material, including the following steps: Step 1: Preparation of confined finishing gel solution Weigh 24.0 g of sodium carboxymethyl-β-cyclodextrin and 360.0 mL of deionized water and add them to the reaction vessel. Stir until dissolved. Then add 5 wt% hydrochloric acid aqueous solution to adjust the pH of the system to 5.8. Then add 10.0 g of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and 6.0 g of N-hydroxysuccinimide and stir. Then add 8.0 g of ε-polylysine and stir at 35 °C for 10 h. After the reaction is completed, add 5 wt% sodium hydroxide aqueous solution to adjust the pH of the system to 6.8. After the reaction is completed, dialyze the solution for 24 h using a dialysis bag with a molecular weight cutoff of 6000 Da. Then filter through a 300 mesh filter and shear disperse at 8000 r / min for 15 min to obtain the confined gel solution.

[0057] Step 2: Preparation of oil- and stain-resistant nonwoven materials

[0058] Weigh 2.4g of tannic acid and 140.0mL of deionized water and add them to the finishing tank. Stir until dissolved, then add 115.0mL of confined finishing gel solution and stir. Then add 10wt% acetic acid aqueous solution to adjust the pH of the reaction system to 5.3, and then add 16.0mL of 5wt% ferric chloride aqueous solution and stir evenly to obtain the composite finishing solution. Weigh out 110.0g of oleophobic grafted nonwoven body and immerse it in 280.0mL of composite finishing solution. Then dry it at 85℃ and heat treat it at 110℃ to obtain an oil- and stain-resistant nonwoven material.

[0059] Example 6

[0060] This embodiment provides a method for preparing a modified fluorine-free oil- and stain-resistant nonwoven material, including the following steps: Step 1: Preparation of confined finishing gel solution Weigh 21.0 g of sodium carboxymethyl-β-cyclodextrin and 315.0 mL of deionized water and add them to the reaction vessel. Stir until dissolved. Then add 5 wt% hydrochloric acid aqueous solution to adjust the pH of the system to 5.5. Then add 8.5 g of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and 5.0 g of N-hydroxysuccinimide and stir. Then add 6.5 g of ε-polylysine and stir at 30 °C for 8 h. After the reaction is completed, add 5 wt% sodium hydroxide aqueous solution to adjust the pH of the system to 6.6. After the reaction is completed, dialyze the solution for 18 h using a dialysis bag with a molecular weight cutoff of 5000 Da. Then filter through a 250 mesh filter and shear disperse at 7000 r / min for 12 min to obtain a confined gel solution.

[0061] Step 2: Preparation of oil- and stain-resistant nonwoven materials

[0062] Weigh out 2.0 g of tannic acid and 122.5 mL of deionized water and add them to the finishing tank. Stir until dissolved, then add 102.5 mL of confined finishing gel solution and stir. Then add 10 wt% acetic acid aqueous solution to adjust the pH of the reaction system to 5.1, and then add 13.0 mL of 5 wt% ferric chloride aqueous solution and stir evenly to obtain the composite finishing solution. Weigh 100.0g of oleophobic grafted nonwoven body and immerse it in 245.0mL of composite finishing solution. Then dry it at 80℃ and heat treat it at 105℃ to obtain an oil- and stain-resistant nonwoven material.

[0063] Comparative Example 1

[0064] The difference between this comparative example and Example 6 is that, in the preparation process of the oleophobic grafted nonwoven body used in step 2, steps ② and ③ are omitted, and the amine-active nonwoven base web prepared in step ① is used to replace the oleophobic grafted nonwoven body in an equal amount.

[0065] Comparative Example 2

[0066] The difference between this comparative example and Example 6 is that the addition of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide was omitted in step one.

[0067] Comparative Example 3

[0068] The difference between this comparative example and Example 6 is that the addition of 5wt% ferric chloride aqueous solution is omitted in step two.

[0069] Performance testing: All performance test samples were flat samples of modified fluorine-free oil- and stain-resistant nonwoven materials prepared in the examples and comparative examples. The samples were cut along a uniform area of ​​the material, avoiding edges, creases, pinholes, and areas with obvious uneven surface finishing. All samples were conditioned for 24 hours under the standard atmospheric conditions specified in GB / T 6529-2008 before testing. Unless otherwise specified, three parallel samples were taken for each group. For grade-related items, the median value of the three parallel samples was taken as the final result, and for numerical items, the arithmetic mean of the three parallel samples was taken as the final result. The term "fluorine-free" in the title of this application is defined by the fact that the finishing system does not introduce fluorine-containing oil-resistant finishing agents, and therefore is not set as a separate evaluation index for this group of performance test items.

[0070] The oil repellency rating is determined in accordance with GB / T 19977-2014 "Textiles - Oil Repellency and Hydrocarbon Resistance Test". The test results are expressed as the oil repellency rating, with the unit being grade. The specific testing method is as follows: Each sample is cut to a size of 200mm×200mm and placed horizontally. Three non-overlapping effective test areas are selected on each sample. Dropping tests are performed sequentially according to the hydrocarbon standard test solution sequence specified in the standard. The oil repellency level of each test area is determined according to the observation time and rating principle specified in the standard. The median level of the three test areas of the sample is taken as the result of the sample. The median value of three parallel samples is then taken as the final result.

[0071] The stain resistance rating is determined by the liquid staining method in GB / T 30159.1-2013 "Textiles - Test and Evaluation of Stain Resistance - Part 1: Stain Resistance". The test results are expressed as the stain resistance rating, with the unit being grade. The specific testing method is as follows: Each sample is cut to a size of 200mm×200mm and evaluated using the liquid staining method. Three non-overlapping valid test sites are selected on each sample. Liquid contaminants are applied according to the standard, and the samples are allowed to stand and rated. The staining resistance level of each test site is recorded. The median level among the three test sites of the sample is taken as the result of the sample. The median value of three parallel samples is then taken as the final result.

[0072] The stain-removability grade was determined by wiping method in FZ / T 01118-2012 "Detection and Evaluation of Stain Repellency of Textiles". The test results are expressed as stain-removability grade, with the unit being grade. This standard includes washing and wiping methods. The results obtained from different stains and different methods are not comparable. Therefore, this application uses the wiping method and the carbon black and oil stains specified in the standard. The specific testing method is as follows: Each sample is cut to a size of 200mm×200mm. Carbon black oil stains specified in the standard are used as the contaminant. 0.05mL of the contaminant is dropped into the effective area in the center of each sample and evenly spread within a diameter of about 10mm. After the sample is laid flat and the contaminant is stably attached, the contaminated area is wiped repeatedly 30 times with a standard lining with a liquid content of 85%. After wiping, the gray scale is used for rating according to the standard. The median value of 3 parallel samples is taken as the final result.

[0073] The air permeability was determined in accordance with GB / T 24218.15-2018 "Textiles - Nonwovens - Test Methods - Part 15: Determination of Air Permeability", and the test results are expressed as air permeability, with the unit being mm / s. The specific testing method is as follows: Each sample is cut to a size of 200mm × 200mm, and a nonwoven fabric air permeability tester is used. The test pressure difference is fixed at 100Pa, and the test head area is fixed at 20cm². 2 Each sample was tested at 5 different locations. The arithmetic mean of the 5 measurements was taken as the result for that sample. The arithmetic mean of 3 parallel samples was then taken as the final result.

[0074] The longitudinal breaking strength was determined in accordance with GB / T 24218.3-2010 "Textiles - Test methods for nonwoven fabrics - Part 3: Determination of breaking strength and elongation at break (strip method)". The test results are expressed as longitudinal breaking strength in N. The specific testing method is as follows: Cut strips along the longitudinal direction of the nonwoven material. The size of a single sample is fixed at 250mm×50mm, with a width of 50mm±0.5mm and a length that meets the nominal clamping distance and clamping requirements of 200mm. The tensile speed is 100mm / min. Five strips are measured for each sample. The arithmetic mean of the five measurements is taken as the result of the sample. The arithmetic mean of three parallel samples is taken as the final result.

[0075] See Table 1 for specific data; Table 1 - Performance Test Data for Each Sample

[0076] Data Analysis: A comparative analysis of the data in Table 1 reveals that the oil-repellent and stain-resistant nonwoven material prepared by this invention has an oil repellency rating of 5, a stain resistance rating of 4, an easy-to-clean rating of 4, and an air permeability of 989 mm². s -1 Meanwhile, the longitudinal fracture strength is 130N, and all data are better than the comparative example, indicating that: In Comparative Example 1, the substrate surface failed to form a transition interface that matched the subsequent finishing layer, resulting in insufficient surface energy distribution, interfacial bonding capacity, and interlayer connection at the fiber outer edge. After the subsequent finishing components entered the surface layer, they were prone to local aggregation, uneven distribution, and unclear bonding layers, making it difficult to construct a continuous and stable composite surface layer. Consequently, oily media were more likely to locally wet the surface and migrate along the pores, and the interfacial constraints during the residence and detachment of pollutants were also weakened, ultimately leading to a decrease in the overall composite response stability.

[0077] In Comparative Example 2, after the activation coupling process is weakened, it is difficult to form a stable and orderly confined correlation structure within the finishing system. The spatial constraint relationship and the degree of synergistic organization between components are reduced accordingly. After the finishing phase enters the fiber surface, it is more likely to exhibit a free dispersion or local enrichment state, making it difficult to form a uniform and continuous control layer along the outer edge of the fiber. Furthermore, the synergistic transfer path between the functional units of the surface is weakened, resulting in a lack of continuous and consistent interface regulation during the contact, residence and subsequent detachment of pollutants. This leads to the loosening of the surface state and causes an overall downward shift in composite performance.

[0078] In Comparative Example 3, after the coordination fixation process was cancelled, although the surface finishing structure could be attached to the outside of the fiber, it was difficult to further complete the interface binding and stable fixation. As a result, the bonding tightness, boundary clarity and spatial stability of the composite layer were limited. Due to the lack of subsequent locking effect, the finishing components were more likely to migrate, redistribute or loosen locally during drying, heat treatment and use. It was difficult to maintain a continuous and consistent surface configuration for a long time. As a result, the synergistic effect of different functional units in the same interface was weakened, which ultimately led to a simultaneous decline in structural retention and composite performance.

[0079] Ultimately, this solution does not simply superimpose different finishing techniques. Instead, it establishes a multi-level action path with sequential connections between substrate interface pre-construction, confined organization of finishing components, and surface coordination fixation. As a result, the interfacial acceptance state of the fiber outer edge, the spatial distribution of functional components, and the ability to maintain the surface structure are incorporated into the same operational chain. This allows the material to exhibit relatively continuous interfacial response characteristics during contact with oily media, contaminant retention, and subsequent use. Correspondingly, when any link is missing, weakened, or the connection is interrupted, the overall surface configuration and its operational stability will become discrete, and the material behavior will also show a different development trend from the overall synergistic configuration.

[0080] The above description is merely an example and illustration of the structure of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described, or use similar methods to replace them, as long as they do not deviate from the structure of the invention or exceed the scope defined in the claims, all of which should fall within the protection scope of the present invention.

[0081] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0082] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a modified fluorine-free oil- and stain-resistant nonwoven material, characterized in that, Includes the following steps: S1. Add tannic acid and deionized water to the finishing tank and stir until dissolved. Then add the confined finishing gel solution prepared by the cross-linking reaction of sodium carboxymethyl-β-cyclodextrin and ε-polylysine under the action of an activator and the subsequent dispersion after post-treatment and stirring. Then add 10wt% acetic acid aqueous solution to adjust the pH of the reaction system to 4.8-5.3, and then add 5wt% ferric chloride aqueous solution and stir evenly to obtain the composite finishing solution. S2. Apply an epoxy oleophobic grafting agent to an amine-activated nonwoven base web, and then perform grafting modification under alkaline conditions through impregnation, drying, and heat treatment. Place the oleophobic grafted nonwoven body into a composite finishing solution for padding, then dry at 75-85℃, and finally heat treat at 100-110℃ to obtain an oil-resistant and stain-resistant nonwoven material.

2. The method for preparing a modified fluorine-free oil- and stain-resistant nonwoven material according to claim 1, characterized in that, In step S1, the ratio of tannic acid, deionized water, confined finishing gel solution and 5wt% ferric chloride aqueous solution is 1.6-2.4g:105-140mL:90-115mL:10-16mL; in step S2, the ratio of oleophobic grafted nonwoven substrate and composite finishing solution is 90-110g:210-280mL.

3. The method for preparing a modified fluorine-free oil- and stain-resistant nonwoven material according to claim 1, characterized in that, The preparation method of the oleophobic grafted nonwoven body is as follows: epoxy oleophobic grafting agent, anhydrous ethanol and deionized water are added to a finishing tank and stirred. After stirring evenly, sodium bicarbonate is added, followed by amine-activated nonwoven base web for impregnation. After impregnation, the liquid is rolled, and post-treatment is performed to obtain the oleophobic grafted nonwoven body. The ratio of the amount of epoxy oleophobic grafting agent, anhydrous ethanol, deionized water, sodium bicarbonate and amine-activated nonwoven base web is 18-24g:145-185mL:18-25mL:0.6-1.0g:90-110g.

4. The method for preparing a modified fluorine-free oil- and stain-resistant nonwoven material according to claim 3, characterized in that, The preparation method of the amine-activated nonwoven base web includes the following steps: A1. Add cellulose short fibers, chitosan short fibers and deionized water to a dispersion tank and disperse them. After uniform dispersion, form a web to obtain a wet fiber web. A2. Add dialdehyde starch, adipic acid dihydrazide and deionized water to a mixing tank and stir. Then add 10wt% acetic acid aqueous solution to adjust the pH of the system to 4.8-5.

4. Then apply it to the fiber wet web, pre-dry it at 80-90℃ after sizing, and then heat treat it at 120-140℃ to obtain amine-activated nonwoven base web.

5. The method for preparing a modified fluorine-free oil- and stain-resistant nonwoven material according to claim 4, characterized in that, In step A1, the ratio of cellulose short fibers, chitosan short fibers, and deionized water is 75-88g:18-24g:3600-4600mL; in step A2, the ratio of dialdehyde starch, adipic acid dihydrazide, deionized water, and fiber wet web is 7-10g:4-5g:180-260mL:90-110g.

6. The method for preparing a modified fluorine-free oil- and stain-resistant nonwoven material according to claim 3, characterized in that, The preparation method of the epoxy oleophobic grafting agent is as follows: polymethylhydrosiloxane and toluene are added to a reaction vessel and stirred. After stirring evenly, allyl glycidyl ether and 1-octadecene are added, followed by platinum catalyst solution. The reaction vessel is heated to 75-85℃ and stirred for 4-6 hours. After the reaction is completed, the solvent is removed under reduced pressure and filtered through a 200-300 mesh filter to obtain the epoxy oleophobic grafting agent.

7. The method for preparing a modified fluorine-free oil- and stain-resistant nonwoven material according to claim 6, characterized in that, The ratio of polymethylhydrosiloxane, toluene, allyl glycidyl ether, 1-octadecene and platinum catalyst solution is 45-60g:100-140mL:10-14mL:15-22mL:0.20-0.25mL.

8. The method for preparing a modified fluorine-free oil- and stain-resistant nonwoven material according to claim 1, characterized in that, The method for preparing the confined finishing gel is as follows: sodium carboxymethyl-β-cyclodextrin and deionized water are added to a reaction vessel and stirred until dissolved. Then, 5 wt% hydrochloric acid aqueous solution is added to adjust the pH of the system to 5.2-5.

8. Subsequently, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide are added and stirred. Then, ε-polylysine is added, and the reaction is carried out at 25-35℃ with stirring for 6-10 hours. After the reaction is completed, 5 wt% sodium hydroxide aqueous solution is added to adjust the pH of the system to 6.3-6.

8. The confined finishing gel is then obtained after post-treatment.

9. The method for preparing a modified fluorine-free oil- and stain-resistant nonwoven material according to claim 8, characterized in that, The ratio of sodium carboxymethyl-β-cyclodextrin, deionized water, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and ε-polylysine is 18-24g:270-360mL:7-10g:4-6g:5-8g.

10. A modified fluorine-free oil- and stain-resistant nonwoven material, characterized in that, The modified fluorine-free oil-proof and stain-resistant nonwoven material is prepared using the preparation method of a modified fluorine-free oil-proof and stain-resistant nonwoven material as described in any one of claims 1-9.